2017
DOI: 10.1002/anie.201703235
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Boroauride: A Donor–Acceptor Complex of Anionic Gold

Abstract: Gold is unique among the transition metals in that it is stable as an isolated anion (auride). Despite this fact, the coordination chemistry of anionic gold is virtually nonexistent, and this unique oxidation state is not readily exploited in conventional solution chemistry owing to its high reactivity. Through the use of a new molecular scaffold based on diboraanthracene (B P , 1), we have overcome these issues by avoiding the intermediacy of zerovalent gold and stabilizing the highly reduced gold anion throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…It was demonstrated that effective DOX release was carried out at pH 4, with stability attained at AuNP diameter close to 20 nm in physiological pH. This strategy can be applied to any drugs possessing complexation ability, such as carboxylates, phosphonates, including anthracycline, alkaloid, and flavonoid . The particle size and pH‐responsive point of nano‐therapeutics are dependent on the complex combinations of polymer ligands, drug molecules, and center metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that effective DOX release was carried out at pH 4, with stability attained at AuNP diameter close to 20 nm in physiological pH. This strategy can be applied to any drugs possessing complexation ability, such as carboxylates, phosphonates, including anthracycline, alkaloid, and flavonoid . The particle size and pH‐responsive point of nano‐therapeutics are dependent on the complex combinations of polymer ligands, drug molecules, and center metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…The weak interaction present in this complex is reminiscent of the weak Au→B bond found in [ A ] + , a complex that also features a redox‐active Z‐type ligand (Figure 1). [9] Indeed the diboraanthracene core is easily reduced by one electron to produce a radical with a notably lengthened Au−B distance. An electronic structure analysis attributes the Au−B distance lengthening in A .…”
Section: Figurementioning
confidence: 99%
“…By analogy with the Au−B bond‐lengthening observed upon reduction of [ A ] + into A . , [9] it is tempting to propose that these conformational changes result from the population of the carbenium accepting orbital such that the C9 atom can no longer act as a Z‐type ligand. Further inspection of the structure reveals a slight puckering of the acridinyl moiety as indicated by a displacement of the C9 carbon atom by 0.26 Å above the plane defined by the C11, C13, and C15 atoms.…”
Section: Figurementioning
confidence: 99%
“…We recently reported the synthesis of the disphosphine tethered diboraanthracene ligand B 2 P 2 (9,10-bis(2-(diisopropylphosphino)phenyl)-9,10-dihydroboranthrene) and a series of its gold complexes in three states of charge. The anionic complex, [Au(B 2 P 2 )][K(18-c-6)] ( 1 ), which features an unprecedented boroauride moiety, could be accessed at remarkably mild potentials (–2.05 V vs. Fc/Fc + , MeCN)23 owing to the formation of a strong 3-centered, 2-electron bond between Au and the two B atoms 24. Considering that 1 can be thought of as a masked borane dianion, we wondered if protonation of this complex could provide direct access to a hydridic B–H unit (Fig.…”
Section: Introductionmentioning
confidence: 99%